Errors in Solving Distance Material on Spatial Figures: Analytical Study on High School Students of Bengkulu Tengah - Hartati, Puji; Agus Susanta; Nurul Astuti Yensi (International Journal of Contemporary Studies in Education, 2024)
Mathematics learning outcomes at the senior high level are still low at the national level. It can be shown that from the result of the Minimum Competence Assessment (MCA) in these two years, the outcome of senior high students is below minimum competence. Problems become the factors of low student competence; one of them is the classroom learning process. In the process of solving that problem, teachers can analyze how students solve the mathematics problems given so the correct method can be figured out.  The purpose of this research is to analyze the errors students make when solving questions about spatial figures and the solutions given to solve the errors. This research is qualitative descriptive research. The subjects in this study were 29 students of class XII of Bengkulu Tengah State Senior High School. These subjects were selected based on the tendency of students to make errors in geometry material. Data were collected through geometry test questions and unstructured interviews. Data are analyzed descriptively and qualitatively. The results of the study showed that students made mistakes in solving geometry problems with visualization errors (34.50%), analysis errors (23.54%), and deduction errors (22.54%). The factors causing the errors made by students were: (1) students were less careful in understanding and analyzing problems, (2) students made mistakes in interpreting problems in the form of images, (3) errors in calculations, (4) students were less careful in making conclusions. Based on the results of this study, it is recommended that teachers in delivering geometry material need to emphasize that students visualize problems with images or geometric constructions so that it is easier to solve problems.